Evaluation of the presence of artificial non-nutritive sweeteners in energy drinks and their risks to the population (Research, Society and Development, 2023)
Sweeteners are natural or synthetic food additives used to sweeten the flavor of products on many levels, used by the food industry to appeal to new audiences. The main objective of this work was to analyze the presence of sweeteners in energy drinks, estimate the consumption of such sweeteners and evaluate the possible risks of excessive consumption. The study analyzed data from ABIR and from the product makers through the ingredient list present on the label of their products. The nutrition information of 122 brands was checked regarding the presence of sweeteners and their type, in which 50,8% of brands did not contain sweeteners, and 49,2% did use them in their formula. Of those, the major types encountered were sucralose e acesulfame-K. Between the labels of brands that used said sweeteners, it was verified if the levels of usage were within regulations. The study detected those five brands regarded as “zero sugar” did not inform the levels of sweeteners in the composition, not complying with national standards. Finally, it was verified that because of the high levels of maximum consumption of each drink found for individuals of 50, 70, and 90 kg, the national apparent consumption does not exceed acceptable daily intake maximum values.